Current prospects of building-integrated solar PV systems and the application of bifacial PVs - Abojela, Zuher R. Khalifa; Desa, Mohd Khairunaz Mat; Sabry, Ahmad H. (Frontiers in Energy Research, 2023)
Building Integrated Solar photovoltaic (BIPV) systems have gained popularity in recent years as a way to improve the building's thermal comfort and generate sustainable energy in building structures. BIPV systems can provide shading against sunshine while generating ancillary electrical power. Over the last decades, researchers have been interested in improving the efficiency of BIPV systems. BIPVs with various installation types including rooftop, balcony, curtain, sunshade, and wall façade types are continuously researched and intensively presented to improve power efficiency and reduce air-conditioning use. This paper presents state-of-the-art solar BIPV systems. An overview and motivations for BIPV systems are initially introduced followed by the survey methodology considered and the contributions. In addition to that, the work classifies the interesting research areas into thermal analysis optimization design and electrical energy yields with their corresponding references. Then, an analytical review of the BIPVs and the existing techniques to optimize the energy yields are discussed to determine the system components that are mostly used, their cost, and their importance in the system. Finally, recommendation amendments to the existing BIPV systems that potentially contribute to increasing the system efficiency, reliability, and cost as future design concepts for the whole system are presented.